The impact of production factors and economic structures on economic development - Tvaronavičienė, Manuela; Lankauskienė, Toma (Business: Theory and Practice, 2013)
The research area of economic growth has passed a long history. Studies on the origin of economic growth date back to the 18th century. Contemporary scientific literature also debates different issues of economy. The presented paper reviews the genesis of the most significant groups of theories about economical growth. The ultimate aim of the presented investigation is to identify the role of economic structures in the process of sustainable development. Hence, following an overview of the main theories of economic development and highlighting a niche of changes in economic structures, the paper focuses on the approaches towards driving forces for changing economical structures. The article also raises a hypothesis about the transformation of production factors that first affect economic growth and then economic structures. It is supposed that the countries having a different level of development, may experience different effect caused by the impact of similar selected driving forces of economic growth, which, in turn, differently restructure national economies.